Intermittent streamflow generation in a merokarst headwater catchment - Hatley, Camden M. (Kansas State University, 2022)
Effective environmental protection strategies for intermittent headwater streams are dependent on first understanding the mechanisms that drive streamflow generation. Previous research in merokarst headwater catchments at the Konza Prairie Biological Station (KS, USA) indicate that intermittent streamflow is fed by multiple surface and subsurface water sources and that threshold behavior in the watersheds contributes to flow intermittency. However, we do not yet understand the relative contributions from each of the water sources nor the specific mechanisms governing the observed threshold behavior. In this study, we employed high-frequency chemical sampling of an intermittent headwater stream and groundwater in a merokarst watershed in the Konza Prairie Biological Station during the 2021 growing season. Our specific goals were to quantify the contributions to streamflow from different water sources, characterize their short-term dynamics, and uncover potential mechanisms behind flow intermittency. Mixing calculations using stable water isotopes indicate that precipitation and surface runoff comprised < 5% of stream flow during most of the sampling period but could comprise > 50% at the peak of large storms when the stream was previously dry. Mixing calculations using major ions indicate that contributions from soil water were < 3% throughout the sampling period and that the dominant contributor was groundwater sourced from two separate perched limestone aquifers. Of the two, the shallower aquifer dominated streamflow generation over most of the study period (39% - 83%), but contributions from the deeper aquifer increased over periods of days to weeks when no precipitation occurred (16% - 60%). During the early period of the study, groundwater contributions from both aquifers were lower than expected based on predictions from stream conditions and groundwater elevations. This discrepancy suggests that groundwater sources are not fully connected to the stream channel until a critical threshold of water storage in the aquifers is attained. Given the dominance of groundwater contributions to streamflow compared to other sources, we hypothesize that this subsurface storage threshold is a major controller of flow intermittency in merokarst headwater catchments.
Keywords: Streamflow generation; Intermittent stream; Merokarst; Groundwater mixing; Concentration-discharge